The strategies of belief in Quentin Tarantino’s The Hateful Eight - Núñez Alberca, Alejandro (2020)
This article proposes a semiotic-structural analysis of Quentin Tarantino's film The Hateful Eight (2015). Our work incorporates elements from filmic narratology, in particular the idea of ​​Emily Anderson's unreliable narrator, which highlights the possibility of an overall unreliable discourse. Our analysis shows that the film, both at the level of the narrative and the discourse itself, presents a series of manipulative simulations that allow its actants to organize the cognitive dimension of knowledge and belief to their advantage. This reveals a device that not only allows characters to deceive others with their speeches, but also the enunciator which operates at a higher level. Therefore, the film transforms underreporting and misreporting into its key tools.